Пошаговое объяснение:
(-2,5-1 5/6): 1 4 /9-3 5/9•(2 1/4)=(-2,5-1 5/6)•4/9-3 5/9•2 1/4=-5/2-1 5/6)•4/9-3 5/9•2 1/4=(-5/2-11/6)•4/9-3 5/9•2 1/4=(5/6-11/6)•4/9-32/9•2 1/4=(5/6-11/6)•4/9-32/6•9/4=-13/3•4/9-32/6•9/4=-13/3•4/9-32•1/4=-13/3•4/9-8=-52/27-8=-268/27
ответ:-268/27
Держи, сделай этот ответ лучшим
Вычисляем определитель матрицы 3×3:
∆ =
2 3 2
5 1 4
1 6 7
= 2·1·7 + 3·4·1 + 2·5·6 - 2·1·1 - 2·4·6 - 3·5·7 = 14 + 12 + 60 - 2 - 48 - 105 = -69.
Находим определители:
∆1 =
5 3 2
1 1 4
0 6 7
= 5·1·7 + 3·4·0 + 2·1·6 - 2·1·0 - 5·4·6 - 3·1·7 = 35 + 0 + 12 - 0 - 120 - 21 = -94.
∆2 =
2 5 2
5 1 4
1 0 7
= 2·1·7 + 5·4·1 + 2·5·0 - 2·1·1 - 2·4·0 - 5·5·7 = 14 + 20 + 0 - 2 - 0 - 175 = -143.
∆3 =
2 3 5
5 1 1
1 6 0
= 2·1·0 + 3·1·1 + 5·5·6 - 5·1·1 - 2·1·6 - 3·5·0 = 0 + 3 + 150 - 5 - 12 - 0 = 136.
ответ: x = ∆1 / ∆ = -94 / -69 = 94 / 69.
y = ∆2 / ∆ = -143 /-69 = 143 / 69.
z = ∆3 / ∆ = 136 / -69 = - 136 / 69.
-11
Пошаговое объяснение:
(-2.5-1 5/6) : 1 4/9 - 3 5/9 × (2 1/4) = -11
По действиям:
1. -2.5-1 5/6 = -2 1/2 - 1 5/6 = -2 3/6 - 1 5/6 = -3 8/6 = -4 2/6 = -4 1/3
2. -4 1/3 : 1 4/9 = -13/3 * 9/13 = -3
3. 3 5/9 * 2 1/4 = 32/9 * 9/4 = 8
4. -3 - 8 = -11